Comprehensive investigation of Litsea cubeba antibacterial and antifungal activities across solid, liquid, and vapor phases against key human pathogens - Sreepian, Preeyaporn M.; Popruk, Supaluk; Rattanasinganchan, Panthip; Sreepian, Apichai (Narra J, 2025)
The escalating global incidence of antimicrobial resistance poses a significant public health challenge. In response, exploring alternative antimicrobial agents, particularly derived from plants, becomes crucial to alleviate the selective pressure exerted by conventional antibiotics. The aim of this study was to characterize the composition of essential oil extracted from Litsea cubeba fruits and to evaluate its antimicrobial potential, along with its major compound, across solid, liquid, and vapor phases. The antimicrobial activity was assessed against a diverse range of human pathogenic Gram-positive bacteria (n=8), Gram-negative bacteria (n=34), filamentous fungi (n=2), and yeast (n=1). Disk diffusion, broth macrodilution, and vapor-phase diffusion methods were employed. This study found that all phases of L. cubeba essential oil and purified limonene exhibited broad-spectrum bactericidal and fungicidal activities (solid-phase: inhibition zone diameter (IZD) 19 mm vs 14 mm; liquid-phase: minimum inhibitory concentration (MIC) 2.0 mg/mL vs 4.0 mg/mL; vapor-phase: IZD 90 mm vs 45 mm), with superior efficacy against filamentous fungi and yeast compared to bacteria (solid-phase: IZD 90 mm vs 17.5 mm; liquid-phase: MIC 2.0 mg/mL vs 0.06 mg/mL; vapor-phase: IZD 90 mm vs 12.5 mm; all p-values<0.05). Among bacteria, solid-phase L. cubeba essential oil demonstrated increased activity against Staphylococcus saprophyticus and Acinetobacter lwoffii whereas liquid-phase L. cubeba essential oil had optimal activity against Streptococcus agalactiae and Elizabethkingia meningoceptica. Notably, Trichophyton rubrum, Nannizzia gypsea, and Candida albicans displayed high susceptibility to all phases of L. cubeba essential oil. These findings highlight the potential activity of L. cubeba essential oil, across its various phases, as a promising alternative antimicrobial agent against medically significant pathogens, providing essential baseline information for further exploration and development of L. cubeba essential oil in the pursuit of combating antimicrobial resistance.